Epidemiological characteristics of COVID-19 in Shenzhen, China: comparison between imported and local cases - Zhihui Li; Jin Wang; Jingyi Huang; Jiahai Lu (Journal of Infection in Developing Countries)
Introduction: An unprecedented outbreak of the novel coronavirus disease (COVID-19) has swept across the globe since the end of 2019. Shenzhen confirmed its first imported case from Wuhan on 19 January 2020. However, little is known regarding the epidemiological characteristics of COVID-19 in these imported cities.